2012
DOI: 10.1155/2012/689291
|View full text |Cite
|
Sign up to set email alerts
|

Warthin-Like Papillary Carcinoma of the Thyroid Gland: Case Report and Review of the Literature

Abstract: We present a case of Warthin-like papillary thyroid carcinoma in a 22-year-old woman and a review of the literature on the topic. The patient had the occasional discovery of a hypoechoic thyroid nodule of approximately 18 mm, characterized by irregular margins, hyperechoic spots, rich intra- and perilesional vascularization, and a suspicious enlarged right laterocervical lymph node. Fine-needle aspiration was performed for both lesions and the diagnosis of papillary thyroid carcinoma without lymph node involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 12 publications
1
32
0
1
Order By: Relevance
“…All WVPTCs in our study were assigned as T1 stage except the last case (case 9) in which conventional PTC larger than 1 cm were accompanied in the ipsilateral lobe with extrathyroidal extension and nodal metastases. Six out of nine patients had no regional nodal metastasis in our study and this result is consistent with previous trend with a lower incidence of nodal metastasis of WVPTC than conventional PTC [7,8]. Coexistences of WVPTC and other variants of PTC might cause worse prognosis because of the unfavorable side among the variants [5,19]; in our study, all two patients who had additional conventional PTCs showed nodal metastases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All WVPTCs in our study were assigned as T1 stage except the last case (case 9) in which conventional PTC larger than 1 cm were accompanied in the ipsilateral lobe with extrathyroidal extension and nodal metastases. Six out of nine patients had no regional nodal metastasis in our study and this result is consistent with previous trend with a lower incidence of nodal metastasis of WVPTC than conventional PTC [7,8]. Coexistences of WVPTC and other variants of PTC might cause worse prognosis because of the unfavorable side among the variants [5,19]; in our study, all two patients who had additional conventional PTCs showed nodal metastases.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the US features of an irregular, elliptical or flat shaped hypoechoic lesion (case 4) resembled to those of focal thyroiditis. Therefore, the seemingly anechoic or marked hypoechoic part itself in the nodule may be correlated with lymphocytic stroma of WVPTC, which is a distinct histological feature distinguishing WVPTC from other types or subtypes of thyroid cancer or cysts which were observed accompanied with lymphocystic stroma in the papillary stalks [5][6][7]. Generally, WVPTC is said to behave like conventional PTC showing good long-term overall survival and rare extrathyroidal extension, nodal metastasis, recurrence or distant metastasis [2,5,6,8,11]; our findings were similar to previous reports showing favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The distinctive feature is the lymphocytic infiltration of the stalks of the papillae as in our case (6,12,13,22). Vascular and capsular invasions are rare.…”
Section: A 1bmentioning
confidence: 64%
“…The macroscopic appearance of WLPTC is generally that of a white-greyish, well-defined nodule and confined to the thyroid gland. It may contain cystic and/or haemorrhagic areas (13). Its mean size for the 58 patients reviewed was 1.7 cm (range 0.3 to 5 cm) ( Table 1).…”
Section: A 1bmentioning
confidence: 99%
See 1 more Smart Citation